A challenging differential diagnosis for Pelizaeus-Merzbacher Syndrome: a literature review (Research, Society and Development, 2022)
In children, white matter disorders are traditionally divided into two main categories: leukodystrophy and leukoencephalopathies. The former are the result of inherited enzyme deficiency that causes abnormal formation, renewal of myelin or destruction. In contrast, leukoencephalopathies involve the destruction of intrinsically normal myelin, with the demyelination mechanism being primarily divided into lysosomal and peroxisomal. In this context, Pelizaeus-Merzbacher Syndrome (PMD) is an X-linked leukodystrophy, characterized by delayed neuropsychomotor development in children. It is a rare disease, predominantly in males, compromising the development and/or maintenance of myelin in the Central Nervous System (CNS). Therefore, the present study aimed to gather scientific articles through a narrative review on Pelizaeus Merzbacher Disease, addressing its classification, pathophysiology, signs and symptoms and the challenges to reach its diagnosis. In this way, this study brings new updates on the disease and helps in directing a differential diagnosis, as well as seeking a better intervention for patients with Pelizaeus-Merzbacher Syndrome.